PENGARUH JUMLAH KUNJUNGAN WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH PROVINSI BALI TAHUN 2004-2022 - Kenneth Olivier; Ida Bagus Suryawan; Made Sukana (Jurnal Ekonomi dan Bisnis, 2026)
Tourism has a role that pivotal function in driving regional economic growth, particularly in Bali Province, which heavily relies on this sector as its primary source of income. Current research examines the effect of international also domestic tourist arrivals on the Regional Original Revenue (Pendapatan Asli Daerah/PAD) of Bali Province over the period 2004-2022. Using a quantitative approach with secondary data from the Bali Provincial Statistics Agency (BPS), current research employs multiple linear regression observation to assess the influence of tourist arrivals on four PAD components: regional taxes, regional levies (retribusi), state-owned enterprise (BUMD) revenue, and other legitimate regional income. Results indicate that domestic tourist arrivals consistently exert a positive then significant effect across all PAD components, while international tourist arrivals exhibit a negative coefficient for most components, reflecting a tendency to use international-brand facilities and digital booking platforms whose revenues are not fully captured in the regional tax system. Simultaneously, both tourist variables significantly influence PAD. These findings underscore the importance of strengthening local tourism governance, optimizing the levy system, and developing strategic policies to maximize the fiscal contribution of international tourists to regional revenue.